Assessment of scallop (Pecten maximus) stocks in the Irish and Celtic seas - Hervás Abad, Antonio (Trinity College (Dublin, Ireland). Department of Zoology, 2008)
Spatially explicit approaches (differing from the traditional stock assessment theory) to the assessment of scallop off the southeast coast of Ireland were developed. Different stock assessments methods were presented with the objective of providing comprehensive information on: (i) the biological parameters and their use in estimating biological reference points (ii) stock indicators to determine the state of the stock. Data for assessment were collected from commercial fishery data for the time period 1995-2004 and data from research surveys for the period 2001-2005.
Keywords: Zoology, Ph.D.; Ph.D. Trinity College Dublin